Modernism and Crisis: Seyyed Hossein Nasr's Idea on Spiritual Intelligence and Its Relevance Today - Suryawan Bagus Handoko; Suteja Suteja; Irfan Hania; Shalahudin Kafrawi (Fakultas Ushuluddin dan Humaniora - UIN Walisongo Semarang, 2023)
Modern humans are experiencing various acute crises. Scientific and technological advancements have ironically become a boomerang for humanity, dominating nature and creating a materialistic and hedonistic lifestyle. This study aims to discover Seyyed Hossein Nasr's perspective on spiritual intelligence and the importance of social virtue education in dealing with modern human problems. This qualitative study employs productive interpretation to analyse the data extracted from the main works of Seyyed Hossein Nasr. This study revealed that Nasr's insights shape a fundamental understanding that promotes spiritual awareness within the educational context, encouraging the integration of spiritual values into the social domain. Such integration will create a more just, empathetic, and environmentally conscious society. Nasr's ideas also provide a pathway to address the challenges posed by modernity by returning to spiritual values and adopting a balanced approach to religion and culture.Contribution: The contribution/urgency that the article gives through this exploration is to shed light on the intricate interplay between spirituality, education, and social values, enriching Nasr's timeless contributions.